A Novel Method of Triple-Wire Gas Indirect Arc Welding. Issue 3 (17th February 2016) - Fang, Disheng; Song, Gang; Liu, Liming
Abstract : This paper proposes a novel triple-wire gas indirect arc welding process. The welding system consists of two power sources and three wires. The effects of the power source mode and the wire configuration on arc stability and behavior are studied. The metal transfer is analyzed and bead-on-plate welding is employed. Results show that two direct current power sources cannot produce a stable process, but the combination of a direct current with a pulsed direct current can produce a stable process. The reason is that the pulsed direct current can boost and stabilize the metal transfer. For the wire configuration, a smaller contact angle between the main wire and the side wire is more desirable. Compared with the traditional gas metal arc welding, this novel process has the advantages of high wire melting rate, low penetration depth, and low dilution rate. Compared with twin-wire gas indirect arc welding, it provides a broader range of applicable currents with sufficient heat input.